Implementasi Program Tabungan Utsman Terhadap Perekonomian UMKM Berdasarkan Peraturan Walikota Bukittinggi - Rizal Fauzan S, Ahmad; Magriasti, Lince (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study aims to analyze the implementation of the Uthman Savings Program based on the Bukittinggi Mayor Regulation in supporting the economy of MSME actors in Bukittinggi City. This program is a form of sharia-based public policy that provides access to financing without interest and collateral to MSME actors, with funding support from the APBD. The research method used is descriptive qualitative with data collection techniques in the form of interviews, observation, and documentation from informants from the City Government, PT BPRS Jam Gadang, and MSME players. In this study, researchers used a qualitative approach with descriptive methods in Bukittinggi City. The results showed that the implementation of the program was quite effective, but still faced several obstacles such as limited human resources, limited budget, and uncooperative customer behavior. The Bukittinggi City Government and PT BPRS Jam Gadang have made a number of solutions such as improving the quality of human resources and improving the supervision system. This program is considered to have a positive impact on increasing access to capital and economic stability of MSME actors, although it still requires strengthening in terms of socialization and supervision.